Tartary buckwheat flavonoids protect hepatic cells against high glucose-induced oxidative stress and insulin resistance via MAPK signaling pathways. Issue 3 (22nd February 2016) - Hu, Yuanyuan; Hou, Zuoxu; Liu, Dongyang; Yang, Xingbin
Abstract : Oxidative stress plays a crucial role in chronic complication of diabetes. Abstract : Oxidative stress plays a crucial role in chronic complication of diabetes. In this study, the protective effect of purified tartary buckwheat flavonoids (TBF) fraction against oxidative stress induced by a high-glucose challenge, which causes insulin resistance, was investigated on hepatic HepG2 cells. Oxidative status, phosphorylated mitogen-activated protein kinases (MAPKs), nuclear factor E2 related factor 2 (Nrf2) and p-(Ser307)-IRS-1 expression, and glucose uptake were evaluated. Results suggest that treatment of HepG2 cells with TBF alone improved glucose uptake and antioxidant enzymes, and activated Nrf2, and attenuated the IRS-1 Ser307 phosphorylation, and enhanced total levels of IRS-1. Furthermore, the high glucose-induced changes in antioxidant defences, Nrf2, p-MAPKs, p-IRS1 Ser307, and IRS-1 levels, and glucose uptake were also significantly inhibited by pre-treatment with TBF. Interestingly, the selective MAPK inhibitors significantly enhanced the TBF-mediated protection by inducing changes in the redox status, glucose uptake, p-(Ser307) and total IRS-1 levels. This report firstly showed that TBF could recover the redox status of insulin-resistant HepG2 cells, suggesting that TBF significantly protected the cells against high glucose-induced oxidative stress, and these beneficial effects of TBF on redox balance and insulin resistance were mediated by targeting MAPKs.